Assessing the market value of a pioneering fruit orchard when comparison data are missing: the Remote Segments Approach - Giuseppe Cucuzza; Laura Giuffrida; Marika Cerro; Maria De Salvo (Journal of Agriculture and Food Research)
In agricultural land appraisal, the absence of comparable transactions poses significant trials, especially when the appraiser oversees the challenge of assessing the market value of an orchard cultivated with pioneering crops in regions where such cultivation is novel. Traditional approaches, like the income capitalization method, struggle due to the lack of valid data, particularly regarding the determination of the capitalization rate. Appraisers often resort to indirect and ambiguous methods for estimating and adjusting rates, leading to unreliable and unrealistic results. This paper proposes, in such cases, the use of the Remote Segments Approach (RSA) as a viable alternative to income capitalization method. By systematically comparing variables between the asset's segment and one or more remote segments, RSA produces more realistic and conservative estimates of the market value when comparable data is unavailable. The case of study relates on the valuation of avocado orchards in Sicily (Italy), a region experiencing the rapid expansion of tropical and sub-tropical fruit cultivations due to climate change. As such innovative crops continue to gain traction in Mediterranean regions, the use of new valuation approaches like RSA in the next future will be crucial for accurately assessing land values and facilitating informed decision-making in agricultural real estate.